SITUS DUPLANG: PEMBELAJARAN BERBASIS MULTIMEDIA ANIMASI INTERAKTIF DI SMA DALAM PERSPEKTIF SEJARAH LOKAL - Abdus Samad; Wiwin Hartanto; Rully Putri Nirmala Puji (LP4MK STKIP PGRI Lubuklinggau, 2020)
Duplang site as a study of local history that teaches field learning or observation of the field. This is done so that in learning students can learn directly about the historic site. In its implementation it is done by observation and the results of the study consist of papers or the like with the intention of students to deepen the learning that he gets. In addition, students agree directly or indirectly to support and more than that to be able to preserve the cultural heritage. The teacher's job is as a facilitator in implementing practices that discuss this local history. In learning local history can help with three forms namely classroom learning, direct observation and in-depth research. The students in this case obtain direct knowledge from the teacher about oral originating from the teacher obtained and then observe directly to be able to deepen and have a direct collection of the historical object. The use of information and communication technology in the context of history becomes a renewal with the teacher who utilizes interactive multimedia in the evaluation process can attract the attention of students and students who can take these historical values. The main purpose of learning local history is to take the values ​​intended for future life and to be able to attract the attention of students to be able to contribute in supporting and preserving the cultural heritage.